(3JMaI GdNdjd aj CNHGQ eUQ hGdfjds - (3eMeO Hf eMeO GdZRGdj, CHh MGeOs
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd GdHdGO GdeUQjI Ydi cKjQ ef GdHdOGf GdN s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B407 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B35 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs